Night of dangers - Clark, Zack Loran; Eliopulos, Nick (Clark, Zach Loran. Adventurers guild, 2020)
A new evil arises in the city of Freestone--Makiva the witch who wants to cause another Day of Dangers that no one will survive. Zed is the only one who can stop her, but he's far from Brock and the others. Then a fatal mistake happens at the market, chaos overtakes the city, and Alabasel Frond fears a threat from within the Adventurers Guild. Brock and Zed try everything in their power to save the city before it's too late.